Penyuluhan tentang Manfaat Kurma (Phoenix dactylifera L.) sebagai Upaya Memperlancar Persalinan - Ulya, Yadul; Herlina, Siskha Maya; Yunika, Regina Pricilia (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
Fluid and nutritional needs are physiological needs that must be properly met by the mother during the birth process. Dates are rich in carbohydrates as a source of energy, influencing the progress of labor, spontaneity in labor and reducing postpartum hemorrhage. Carbohydrates as amplifiers are sugars that are absorbed and used by the body's cells shortly after consumption. Dates also contain B vitamins, minerals, iron, calcium, magnesium, potassium, saturated fatty acids and unsaturated fatty acids. Fatty acids besides providing energy also help provide prostaglandins. Fatty acids can help store energy and strengthen the uterine muscles. Dates also contain hormones that can stretch the uterus when approaching the birth of a baby. Therefore it is necessary to do counseling about the benefits of dates (Phoenix dactylifera L.) as an effort to facilitate labor. The activity of providing counseling about the benefits of dates (Phoenix dactylifera L.) as an effort to facilitate childbirth was carried out in Jempong Baru Village, Sekarbela District, Mataram City and was attended by 20 pregnant women. The results of the pretest and posttest showed an increase in pregnant women's knowledge about the benefits of dates (Phoenix dactylifera L.) as an effort to facilitate labor.